Visceral Fat Dysfunctions in the Rat Social Isolation Model of Psychosis - Schiavone, Stefania; Camerino, Giulia M.; Mhillaj, Emanuela; Zotti, Margherita; Colaianna, Marilena; De Giorgi, Angelo; Trotta, Antonello; Cantatore, Francesco P.; Conte, Elena; Bove, Maria; Tucci, Paolo; Morgese, Maria G.; et al. (Frontiers in Pharmacology, 2017)
Medication with neuroleptics has been associated with adipose tissue dysfunctions and, in particular, with increased visceral fat amount. However, several studies suggested that antipsychotic treatment might not be the main responsible of fat mass accumulation, as this has been also described in not treated psychotic patients. One of the most used “drug-free” rodent models of psychosis is the social isolation rearing of young adult rats, which provides a nonpharmacologic method of inducing long-term alterations reminiscent of symptoms seen in psychotic patients. Recent data highlighted a crucial role of redox imbalance in adipose tissue dysfunctions, in terms of decreased antioxidant defence and increased reactive oxygen species (ROS). Here, we investigated possible oxidative stress-related biomolecular alterations associated with visceral fat increase in seven week isolated rats. To this purpose, we quantified total and visceral fat amount by using dual-energy X-ray (DEXA) absorptiometry. On visceral fat, we analysed the expression of specific ROS-producer genes (Nox1, Nox4, Hmox-1), antioxidant enzymes (Prdx1 and Ucp-1) and oxidative stress-induced damage markers (Cidea, Slc2a4 and Acacb) by Real-Time PCR. The impact of oxidative stress on beta3-adrenergic receptors was also assessed. We found that seven weeks of social isolation induced an increase in total and visceral fat, associated with a decrease in Prdx-1 and Ucp-1 mRNA levels and an enhanced expression of Nox1 and Hmox-1. No differences were detected in Nox4 mRNA levels between grouped and isolated animals. Elevations in Cidea, Slc2a4 and Acacb expression in visceral fat of isolated animals accounted for oxidative stress-related damage in this tissue, further associated with a significant increase in adrenergic beta-3 receptor (Adrb3) mRNA. Our results provide a novel understanding of the pathological link existing among psychosocial stress-induced psychosis, adipose tissue dysfunctions and redox imbalance, opening new therapeutic perspectives for the treatment of alterations in peripheral tissues associated with this mental disorder.